A geometria do origami como ferramenta para o ensino da geometria euclidiana na educação básica - Barreto, Carlos Alberto (2013)
The purpose of this monograph is to study the geometry of origami and its applications in Euclidean Geometry as a tool that contributes to the teaching of Geometry in Basic Education. Provide a brief history of origami and its arrival in Brazil and as a result we present the axioms that define the simple movements that can be performed using points and straight lines in a plane. We also study the classic problems of doubling the cube and the trisection of the angle, showing that they are possible to be solved through the Geometry of Origami. We show then the Origami applications for studies of flat Euclidean space, emphasizing the study of Plato polyhedra. We finished the job by showing how we developed the Origami Project - Mathematics and Art in the State College John XXIII .